Mānavatece pujārī Rāshṭrasanta Tukaḍojī - Kaḍave, Raghunātha (Rāshṭrasanta Tukạdojī Sāhitya Pracāra Maṇḍaḷa, 1981)
Biography of Tukdoji Maharaj, 1909-1968, Hindu religious and social leader from Maharashtra.